Design of Ti6Al4V-HA composites produced by hot pressing for biomedical applications. (15th October 2016) - Miranda, G.; Araújo, A.; Bartolomeu, F.; Buciumeanu, M.; Carvalho, O.; Souza, J.C.M.; Silva, F.S.; Henriques, B.
Abstract: In order to enhance osteointegration, prostheses surfaces are usually coated with bioactive materials like hydroxyapatite (HA), material found in teeth and bones. Traditional HA coatings were proven adequate for obtaining high-quality coatings on metal substrates. However, due to the implantation process, these coatings can be detached from the metal surface. In this work, a new materials design that aims to avoid this coating detachment scenario is proposed, based on composites of Ti6Al4V alloy reinforced with HA powder, with materials gradation from bulk to surface of the prosthesis, where the titanium bulk provides toughness and the outer regions provide biological performance. In order to assess the mechanical and biological performance of the prosthesis outer region, Ti6Al4V-HA composites with different HA contents were produced and characterized regarding microstructure and mechanical properties. Shear tests were performed and fracture surfaces were analysed. EDS and XRD analysis were performed in order to assess HA possible decomposition due to processing temperature and pressure during the hot pressing route. This work shows that the combination of hot pressing technique and an FGM design approach is a promising solution for manufacturing prosthesis with improved bioactivity that can overcome the detachment problems of solutions based on HA coatings. Graphical abstract: Highlights: Ti6Al4V-HA composites with 5 and 10 vol.% HA were successfully produced by hot pressing. The hot pressing process promoted an effective consolidation of the Ti6Al4V matrix, without leading to HA degradation. These Ti6Al4V-HA composites exhibited a good distribution of HA bioactivity sites. An FGM design approach is proposed for manufacturing prosthesis with improved bioactivity for promoting osteointegration. This design approach for manufacturing Ti6Al4V implants can overcome the detachment problems of HA coatings solutions.